Interaction of phenolic compounds with pectinases from Sclerotinia sclerotiorum - and GIRIDHAR SONI, SUCHETA SHARMA, HARMANDEEP (Indian Phytopathology, 2002)
Activities of both pectinases (polygalacturonase and pectin methyl esterase) from Sclerotinia sclerotiorum increased with the growth period of fungus upto 7 days of growth and declined as the growth period was further progressed. Polygalacturonase (pG) and pectin methyl esterase (PME) had pH optima of 5.2 and 5.0 and maximum activity at 35Â°C and 45Â°C temperatures respectively. Activities of these enzymes were in general inhibited by divalent metal ions. However, Mg++ stimulated activities of both the enzymes. Both PG and PME were inhibited by phenolic compounds viz. m-coumaric, homovanillic and protocatechuic acid. The activities of these enzymes also decreased when phenolicextracts of resistant variety of pea (Pisum sativum) seeds and neem (Azadirachta indica) leaves were incorporated in the culture medium. These results suggest the role of phenolics in disease resistance.